If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + 5x = 23 Solving 18 + 5x = 23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 5x = 23 + -18 Combine like terms: 18 + -18 = 0 0 + 5x = 23 + -18 5x = 23 + -18 Combine like terms: 23 + -18 = 5 5x = 5 Divide each side by '5'. x = 1 Simplifying x = 1
| f+2f+9f=156 | | V^2-14+48=0 | | 0.5t^2-3t=0 | | 13y-2=y+10 | | -6x+18=9x-12 | | 9w+3=3(9+w) | | d=.5kq | | 3e^2x+12=42 | | x=2.5(x-15) | | 17x+15=25 | | 3*7x=10.48 | | 9x-18=-180 | | 5t+10=5(t+10) | | X^2+14+16=0 | | x^2+28x+12=0 | | 0=r^2-144.49 | | 2x^4+6x^2-1=0 | | 7.94=2r*3.14 | | -2x-9x=x | | 6x+10=-35-3x | | 7.94=2pir | | -3-6=-33 | | -5/7x=3 | | m+287=500 | | 2x-x+20=40 | | 48-p=3p+4 | | 24-2x=14-24 | | 96+m=249 | | -4(a+5)-6(12a-30)=0 | | 96+m=246 | | 5x-14=4x+17 | | 3(x-3)-2=3x+2 |